Calvyn en die kerklike orde: Enkele opmerkings - Pont, A. D. (Hervormde teologiese studies, 1986)
Calvin and Church Order: Some remarks In commemoration of the publishing of Calvin's Institutes in 1536 and in a tribute to Prof Dr PS Dreyer, some of the main principles of Calvin’s church order are discussed. It is pointed out that the christological centre of the church occupied Calvin's attention more than the peripheral question of discipline.